New specie of Neoparasitylenchus (Tylenchida, Allantonematidae), parasitizing Harmonia axyridis (Coleoptera, Coccinellidae) from Argentina - Camino, Nora Beatriz (2020)
Presence of the genus Neoparasitylenchus Nickle, 1967 (Tylenchida, Allantonematidae), parasitizing Harmonia axyridis (Pallas, 1773) (Coleoptera, Coccinellidae) in Argentina. We describe a new species Neoparasitylenchus platense sp. n., which is characterized by having the free living stages lip region flatly rounded, spear slender, faintly knobbed, tail rounded, females with light brown body, stylet not sunken into body, and not prominent, subterminal vulva and anus, obtusely rounded tail end, with a peg-like projection, oviparous, and the males with a little stylet and partially degenerate oesophagus, spicules filiform with widened base, short gubernaculum, leptodera bursa. ________________________________________________________________Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:FBE9DC98-04C4-4074-9037-1F5979320E2FActo nomenclatural/nomenclatural act:Neoparasitylenchus platense Camino, Reboredo & González, 2020LSIDurn:lsid:zoobank.org:act:B1146E52-46CC-40D0-B9FA-6627EA3B53E7________________________________________________________________